2018
DOI: 10.1038/s41598-018-35547-5
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and mutational analyses of human LEUTX, a homeobox gene implicated in embryogenesis

Abstract: Recently, human PAIRED-LIKE homeobox transcription factor (TF) genes were discovered whose expression is limited to the period of embryo genome activation up to the 8-cell stage. One of these TFs is LEUTX, but its importance for human embryogenesis is still subject to debate. We confirmed that human LEUTX acts as a TAATCC-targeting transcriptional activator, like other K50-type PAIRED-LIKE TFs. Phylogenetic comparisons revealed that Leutx proteins are conserved across Placentalia and comprise two conserved dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 84 publications
2
32
2
Order By: Relevance
“…We identify several arrays of tandem ETCHbox duplicates, one of the largest of which is an array of LEUTX loci in O. cuniculus . Previous work detected six loci (Katayama et al 2018 ), whereas we detect 27 gene copies in the assembly analysed, of which 14 are putatively functional, 11 are putative pseudogenes and two are of uncertain functional status (Online Resource Fig. S1).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…We identify several arrays of tandem ETCHbox duplicates, one of the largest of which is an array of LEUTX loci in O. cuniculus . Previous work detected six loci (Katayama et al 2018 ), whereas we detect 27 gene copies in the assembly analysed, of which 14 are putatively functional, 11 are putative pseudogenes and two are of uncertain functional status (Online Resource Fig. S1).…”
Section: Resultsmentioning
confidence: 75%
“…However, this analysis was limited by sparse phylogenetic coverage and the low-quality genome assemblies available at the time. Katayama et al ( 2018 ) performed a deeper analysis of LEUTX evolution, but this study was restricted to the one gene and without analysis of gene loss. Recent improvements to long-read DNA sequencing mean that many additional mammalian genome sequences are now available, assembled to high contiguity and accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, colocalization of KDM4E with LEUTX expression in the same myotube is consistently better than with DUX4 expression (Figure 5d). Motif analyses revealed that the promoter region of the KDM4E gene contains not only the DUX4 binding motif but also multiple sites of the putative LEUTX binding motif (Figure S6) (Jouhilahti et al, 2016; Katayama et al, 2018). These results raise the possibility that LEUTX may be involved in KDM4E upregulation.…”
Section: Resultsmentioning
confidence: 99%
“…DUX4 comprises two homeodomains and an intrinsically disordered region with three regions of predicted low disorder conserved in primates. Two predicted amphipathic helices contain a nine amino acid transactivation domain (9aaTAD 20 ), also present in LEUTX 21 , and a motif known to recruit the KIX domain 22 of the cAMP-response element binding protein (CREB)-binding protein (CBP) 23 (Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%